Syphilis and Beyond: A Comprehensive Analysis of Associated Infections and Comorbidities in a Five-Year Retrospective Study in the United Arab Emirates (2018-2022) - Nargis, Khatoon Hossein Mehdi Poor; Laila, Mohamed Jasim Ali AlDabal; Safia, Bashiri; Elham, Alneaimi; Afra, Ahmad Abdulla Alshafar Almarri; Amani, Mohamed Saeid Bayoumy; SalahEldin, Hussain Omer; Carol, Lavina Dsouza; Musthafa, Moosa (International Journal of Sexually Transmitted Diseases, 2024)
Objectives This study explores the clinical characteristics, associated infections, and management outcomes of syphilis within a specific population over the years 2018 to 2022. With a focus on the frequency, clinical manifestations, and co-infections of syphilis, the research addresses a critical gap in understanding the nuanced dynamics of this sexually transmitted infection and its impact on public health. Methods The study employs a retrospective analysis of data collected from 2018 to 2022, utilizing three key serological tests (Syphilis AB, RPR/VDRL, and TPHA) to characterize syphilis infections within the population. Clinical manifestations and associated infections, including HIV, HBV, HCV, Chlamydia, Gonorrhea, and HPV, are systematically assessed. Treatment rates and re-infection patterns are also analyzed, providing a comprehensive overview of syphilis epidemiology within the studied timeframe. Results The frequency of syphilis, particularly indicated by the Syphilis AB test, exhibited a marked increase in 2020, reaching 96%, suggesting a heightened frequency within the population. RPR/VDRL test results demonstrated consistent frequency, emphasizing the persistent presence of active syphilis infections. Clinical manifestations, such as chancre, skin rashes, alopecia syphilitica, and lymphadenopathy, displayed dynamic patterns over the study years. Co-infection rates varied, with fluctuations observed in HIV, Chlamydia, Gonorrhea, and HPV, while HBV and HCV showed infrequent but stable frequency. The management of syphilis cases demonstrated commendable treatment rates, but an increase in re-infection rates in 2021 highlights the need for continued vigilance. Conclusion This study provides a comprehensive evaluation of syphilis epidemiology, clinical characteristics, and associated infections within the studied population. The results offer valuable insights into the dynamic nature of syphilis and its co-infections, informing public health initiatives and interventions. The findings contribute to our understanding of the epidemiological landscape and underscore the importance of sustained efforts in both prevention and treatment to curb the transmission of syphilis and its associated infections. The study, however, calls for continued vigilance and research to address the evolving trends and challenges in syphilis management within the specified population.
Keywords: Syphilis; Retrospective analysis; Comorbidities; Associated infections; Sexually transmitted illness